Buoyant Energy—balancing wind power and other renewables in Europe's oceans. (December 2017) - Klar, Robert; Steidl, Bernd; Sant, Tonio; Aufleger, Markus; Farrugia, Robert N.
Abstract: Buoyant Energy is a new approach to store electrical energy offshore and decentralized, based on the well-established technologies of pumped-storage hydropower. This paper focuses on the basic concept and deals with some key features this new storage solution provides. Subsequently to the explanation of the main functionality of the storage concept other important parameters like the efficiency (more than 80% are estimated), the storage capacity (approximately 1 MWh for a solution with the dimensions of 50 × 50 × 38 m) and the high adaptability that provides numerous possible locations are discussed. This is followed by a basic cost assessment which demonstrates the economic feasibility for three different scenarios. The results indicate, that the break-even point is reached between 5 and 30 years but in each case within the proposed lifetime of 50 years and more. The final case study evaluates the effects of integrating deep offshore wind power balanced by integrated Buoyant Energy units. The rising flexibility of the overall system and the direct conversion of the intermittent to a constant power source over a pre-determined period are some benefits as shown in the results.